2019
DOI: 10.2147/ijn.s203507
|View full text |Cite
|
Sign up to set email alerts
|

<p>Extracellular vesicles released by J774A.1 macrophages reduce the bacterial load in macrophages and in an experimental mouse model of tuberculosis</p>

Abstract: BackgroundTuberculosis is the leading cause of death by an infectious microorganism worldwide. Conventional treatment lasts at least six months and has adverse effects; therefore, it is important to find therapeutic alternatives that reduce the bacterial load and may reduce the treatment duration. The immune response against tuberculosis can be modulated by several mechanisms, including extracellular vesicles (EVs), which are nano-sized membrane-bound structures that constitute an efficient communication mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 45 publications
0
14
2
Order By: Relevance
“…Indeed, EV from macrophage infected with M. bovis modulated T lymphocytes responses ( 412 ). When macrophages were infected with M. tuberculosis , the content of the EV changed to confer decreased inflammatory cytokine release and decrease lung mycobacterial load ( 413 ). Furthermore, during infection with hepatitis C virus, macrophages secreted EVs that inhibited viral replication ( 414 ).…”
Section: Mechanisms Used By Macrophages To Kill S Aureusmentioning
confidence: 99%
“…Indeed, EV from macrophage infected with M. bovis modulated T lymphocytes responses ( 412 ). When macrophages were infected with M. tuberculosis , the content of the EV changed to confer decreased inflammatory cytokine release and decrease lung mycobacterial load ( 413 ). Furthermore, during infection with hepatitis C virus, macrophages secreted EVs that inhibited viral replication ( 414 ).…”
Section: Mechanisms Used By Macrophages To Kill S Aureusmentioning
confidence: 99%
“…In contrast, both EVs decreased the bacterial lung load in vivo. These results are the foundation for more investigations to assess whether EVs enhance the efficacy of the conventional therapy for tuberculosis (TB) (García-Martínez et al 2019 ) The recent evidence has indicated that the Mtb infection can enhance microvesicle generation in response to iron limitation. These microvesicles carry mycobactin, which can work as an iron donor and promotes the replication of iron-starved mycobacteria.…”
Section: Role Of Exosome In Mycobacterium Tuberculosis mentioning
confidence: 99%
“…The detection of this potential lipid biomarker in both AnxA1 -/supernatants (LPS and nigerin) can be related to the release of extracellular vesicles by macrophages. Macrophages can release extracellular vesicles after Mycobacterium tuberculosis infection, or spontaneously with a high concentration of phosphatidylserine [65].…”
Section: Discussionmentioning
confidence: 99%